Antrodia camphorata Induces Apoptosis and Enhances the Cytotoxic Effect of Paclitaxel in Human Ovarian Cancer Cells. Issue 7 (1st October 2011) - Liu, Fu-Shing; Yang, Pei-Yu; Hu, Dan-Ning; Huang, Yen-Wen; Chen, Miao-Ju
Abstract : Introduction: Antrodia camphorata is a Chinese herb. Recently, several reports demonstrated that it had growth-inhibiting effects on some cancer cells. In this study, we investigated whether the crude extract of A. camphorata could inhibit the growth of ovarian cancer cells and examined the possible mechanisms involved. We also examined whether the cytotoxic effect of paclitaxel on ovarian cancer cells would be affected by A. camphorata . Materials and Methods: Two human ovarian cancer cell lines, SKOV-3 and TOV-21G, were treated with A. camphorata (3-300 μg/mL). An MTT assay was used to test its cytotoxic effect. The apoptosis-related factors including the activity of caspase-3, -8, and -9 and the cytochrome c level released from mitochondria were analyzed. The expression of Bcl-2 family proteins (Bcl-2, Bcl-xL, Bax, Bim, Bad, and Bak) was examined by Western blot analysis. Cell lines were further treated with paclitaxel or paclitaxel plus A. camphorata to examine the cytotoxic efficiency. Results: The MTT assay revealed that A. camphorata was cytotoxic to both the ovarian cancer cells in a dose- and time-dependent manner. Activities of caspase-3, -8, and -9 and release of mitochondrial cytochrome c increased in both ovarian cancer cell lines with increased dose of A. camphorata . Western blot analysis of Bcl-2 family proteins revealed an increased expression of Bad in SKOV-3 cells, whereas increased expression of Bim and Bak and decreased expression of Bcl-xL were noted in TOV-21G cells. In addition, the cytotoxic effect of paclitaxel on SKOV-3 and TOV-21G cells was increased significantly with the addition of A. camphorata ( P < 0.01) by MTT assay. Conclusions: These in vitro results suggest that A. camphorata causes a cytotoxic effect on ovarian cancer cells through the induction of apoptosis. It may also enhance the antitumor effect of paclitaxel. Further studies with the ultimate goal of conducting clinical trials are warranted.